Binding affinity of family 4 carbohydrate binding module on cellulose films of nanocrystals and nanofibrils. (1st January 2021) - Liu, Tian; Zhang, Yu; Lu, Xiaomin; Wang, Peipei; Zhang, Xinyu; Tian, Jing; Wang, Qingcheng; Song, Junlong; Jin, Yongcan; Xiao, Huining
Graphical abstract: Highlights: van't Hoff analysis was employed to assess ΔH, ΔS and ΔCp. CBM4 binds to both CNC and CNF but with different modes. Binding of CBM4 on CNF is mainly enthalpically driven while entropically on CNC. Negative ΔCp for the CBM4 binding to CNF while positive to CNC. Abstract: The binding affinity and thermodynamics of family 4 carbohydrate-binding module (CBM4), belonging to type B CBM, on model surfaces of cellulose nanocrystals (CNC) and nanofibrils (CNF) were investigated by quartz crystal microbalance with dissipation monitoring (QCM-D) technology in real-time at different temperatures. The thermodynamic parameters associated with the interaction, such as Gibbs free energy, enthalpy change, entropy change and heat capacity were obtained using the van't Hoff analysis via a nonlinear parameter estimation. The results demonstrated CBM4 binds preferentially to both CNF and CNC, whereas the driving forces behind them were very different. The former was related to the hydrogen bonds formed in the CBM4 clefts, resulting in a favorable enthalpy but compensated by unfavorable entropy change; on the contrary, the latter was mainly driven by favorable entropy but compensated by unfavorable enthalpic change due to water rearrangement.